Numerical simulation of losses and heating in the constructional elements of transformers of ferromagnetic steel - Ivankov, V.F.; Basova, A.V.; Khimjuk, I.V. (Технічна електродинаміка, 2014)
The application of the methods of calculation of surface and volume losses in the constructional elements of transformers of ferromagnetic steel is considered. A brief description of the developed practical procedures of their calculation using the ANSYS software is given. The testing results of the proposed procedures conducted on the known experimental studies TEAM21, as well as calculation samples of losses and heating in the constructional elements of a singlephase autotype transformer with capacity of 500 MVA and reactor of ROM type with capacity of 80 MVAr, are provided. В роботі розглянуто застосування методів розрахунку поверхневих і об’ємних втрат в елементах конструкції трансформаторів з феромагнітної сталі. Подано короткий опис розроблених практичних процедур їхнього розрахунку із застосуванням програмного забезпечення ANSYS. Наведено результати тестування запропонованих процедур на відомих експериментальних дослідженнях ТЕАМ21, а також приклади розрахунку втрат і нагрівів в елементах конструкції однофазного автотрансформатора потужністю 500 МВА і реактора типу РОМ потужністю 80 МВАр. В работе рассмотрено применение методов расчета поверхностных и объемных потерь в элементах конструкции трансформаторов из ферромагнитной стали. Дано краткое описание разработанных практических процедур их расчета с применением программного обеспечения ANSYS. Приведены результаты тестирования предложенных процедур на известных экспериментальных исследованиях ТЕАМ21, а также примеры расчета потерь и нагревов в элементах конструкции однофазного автотрансформатора мощностью 500 МВА и реактора типа РОМ мощностью 80 МВАр.